Primary Liver Small Cell Carcinoma Masquerading as Cholangiocarcinoma - A Rare Case Report - Hardas, Gauri Vinod; Prasad, Saurabh (Annals of Pathology and Laboratory Medicine, 2024)
Primary liver small cell carcinoma is a rare malignancy with poor prognosis. Our patient, 44 years old male presented with the symptoms of abdominal pain, decreased appetite & black colored watery stool since one month. On PET -CT he had multiple rounded lesions in liver which were thought to be cholangiocarcinoma initially. Biopsy & immunohistochemistry were performed & it was found to be small cell carcinoma. Patient was managed with chemotherapy. Being rare, it is necessary to do proper typing of such tumor so that patient gets benefited by specific treatment. Further, it also helps to know the prognosis.